Development of Stock Companies - Šimėnas, Albertas (Ekonomika, 1999)
A variety of forms of managing economy has become characteristic for Lithuania due to the functioning of market economy. The biggest role in the economic life is played by the joint-stock and close companies. The activities of the companies and at the same time general economic activity in the country are affected by the pitfalls in legal regulation of company activities. The development of the joint-stock companies has shown that each inaccuracy or flaw of a legal act deforms economic life by either decreasing efficiency of utilisation of material and financial resources of the company and at the same its income or gives it all necessary preconditions for increasing the income of the company in a dishonest way by violating the interests of other economic entities and those of the state and even by appropriating the property and funds of the company. It is a negative trend with the view of economy on the whole. Economic relations undergo a very dynamic development during the time of the reforms, therefore, the laws adopted are subject to rapid “ageing.” Consequently, the necessity matures to improve laws and legal acts respectively upon reaching certain stage of development. The countries which have deep traditions of market economy have accumulated a lot of experience in legal regulation of all forms of economic activity, which could and has to be used. Unfortunately, due to the differences in the level of market relations development even the comparatively perfect foreign laws and legal act cannot be mechanically transposed and applied. The Law on Joint-Stock Companies of the Republic of Lithuania was adopted on 30 July 1990. State-owned enterprises which had dominated until that time were replaced by state-owned stock companies where the state owned more than 50 per cent shares. The right to govern in these enterprises was granted to private shareholders and employees of the enterprises, whereas the liability for the outcome of activity has not been provided for the latter. The enterprises operated inefficiently and their property and income were misappropriated. The Law on Joint-Stock Companies of 5 July 1994 was basically amended and the state joint-stock companies were reorganised to joint-stock companies. The practice of economic life has shown that property and non-property rights of shareholders, particularly of those small, are insufficient as well as the control over the activities of the company’s management and liability for the performance of the company. To remove deficiencies, the Law on Joint-Stock Companies was correspondingly amended on 17 April 1998. Moreover, the joint-stock companies have received the right to pay their debts to the state budget with their property and shares. 1n addition, special shares have been legitimised, which grant the state additional non-property rights in the privatised enterprises. These provisions fail to comply with the EU directives and, thus, should be revoked in the immediate future.